Perbandingan Penggunaan Metode Sainte Lague dan Kuota Hare pada Negara Indonesia-Korea Selatan-Irak - Salsa Zahrotun (Staatsrecht: Jurnal Hukum Kenegaraan dan Politik Islam, 2023)
This research discusses methods for calculating election votes. The aim of this research is to find out the differences in method use in each country. The use of election vote counting methods varies by country, the ones highlighted in this article are the Sainte Lague method and the Hare quota. Sainte lague is converting the results of valid votes by dividing them using a certain number, while hare quota is converting election results by reducing the results of valid votes by the price of one seat. In this research, differences in the use of vote conversion are due to the assumptions of each country regarding the effectiveness value of each method so that each country has its own method. In this study, it is stated about the differences in each country in using each election model, be it Saint Lague and Hare quota. Because the basis for using the election model is based on the conditions and political developments in each country. Although for example in Indonesia, Iraq and South Korea use their respective model choices. The model used still has advantages and disadvantages as evidence of the plurality of political problems in each country that are diverse. But regardless of the advantages and disadvantages, the use of the election model shows the seriousness of each country to improve its electoral democracy.   Abstrak Penelitian ini mambahas tentang metode dalam perhitungan suara pemilu, tujuan dari penelitian ini adalah untuk mengatahui perbedaan penggunaan metode pada tiap negara. Penggunaan metode perhitungan suara pemilu berbeda tiap negara, yang disoroti dalam artikel ini adalah metode sainte lague dan kuota hare. Sainte lague adalah mengkonversi hasil suara sah dengan membaginya menggnakan bilangan tertentu, sedangkan kuota hare adalah pengonversian hasil pemilu dengan mengurangi hasil suara sah dengan harga satu kursi. Dalam penelitian ini dikemukakan mengenai perbedaan dalam setiap negara dalam menggunakan masing-masing model pemilihan, baik itu saint lague dan kuota hare. Karena memang dasar penggunaan model pemilihan berdasarkan kondisi dan perkembangan politik di tiap negara. Meskipun sebagai contoh di Indonesia, Iraq dan Korea selatan menggunakan pilihan modelnya masing-masing. Tetaplah model yang digunakan memiliki kekurangan dan kelebihan sebagai bukti pluralitas permasalahan politik di tiap negara yang beraneka macam. Tetapi terlepas dari kekurangan dan kelebihan, penggunaan model pemilihan menunjukkan keseriusan tiap negara untuk memperbaiki demokrasi pemilihannya